Pengembangan Aplikasi Pengelola Referensi Skripsi Mahasiswa Universitas Negeri Malang berbasis Personal Information Management - Hisyam Manusakerti; Moh. Safii; Didin Widyartono (Institut Agama Islam Negeri (IAIN) Curup, 2022)
The compilation of reference documents for the thesis can be collected in large numbers. Documents collected in large numbers that not accompanied by good document management can cause